High Security System Provided By Steganographic Technique Using Palm and Iris Scan (International Journal of Engineering and Computer Science, 2014)
The project proposes to implement the biometric security system based on combination of iris and palm print with steganographic technique for authentication purpose. Here the data hiding approach involves to conceal secret personal informatics within their biometric for still enhance the privacy protection.